Motivations Driving Thai BIPA Students to Learn Indonesian Language in Java Region Indonesia - Abdulrohim E-sor; Laili Etika Rahmawati; Markhamah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the motivational profiles of Thai students enrolled in the Indonesian Language for Foreign Speakers (BIPA) programs across the Java region, Indonesia. Using a mixed-methods case study design, data were collected from 101 Thai learners through structured Likert-scale questionnaires and open-ended survey questions. Quantitative data were analyzed using IBM SPSS, while qualitative responses were examined through thematic analysis. The findings indicate a strong motivational structure among participants, reflected in both integrative and instrumental motivation. Integrative motivation, associated with cultural engagement and social interest, emerged as the dominant factor (M = 3.94), while instrumental motivation related to academic achievement and career opportunities also showed a high level (M = 3.69). The research instruments demonstrated strong internal consistency, with Cronbach’s Alpha values ranging from 0.793 to 0.861, indicating high reliability and validity. Qualitative findings further revealed that positive attitudes toward Indonesian people and strong personal connections with Indonesian culture significantly enhanced students’ learning persistence. These findings highlight the importance of balancing linguistic competence and cultural immersion within BIPA curricula. Furthermore, the study offers a framework for pedagogical improvement and recommends future research to explore the hybrid motivational identities of Southeast Asian learners.